Evaluasi CPPB IRT dan Penyusunan Rekomendasi HACCP pada UMKM Tempe a-Zaki di Bandar Lampung - Ulfa, Masayu Nur; Wahyuningtyas, Amalia; Marvie, Ilham; Pangastuti, Hesti Ayuningtyas (Communication in Food Science and Technology, 2022)
Tempeh is a fermented food composed primarily of soybeans that is a nutrient-dense, cost-effective, and sustainable functional source of protein. Tempeh production, especially in Indonesia, is done usually in household scale. For its development, the producers should be maintaining their product quality, especially in food safety management such as good manufacturing pratices (GMP) and Hazard Analysis Critical Control Point (HACCP). The objectives of this study was to identify the suitability of GMP implementation and to compose HACCP plan. This study took place in a-Zaki tempeh household producer in Bandar Lampung. This study was conducted with descriptive quantitative approach. Primary data (observations and interviews) and secondary were collected as the information.. For GMP evaluation, the obtained data was compared with the regulation of food and drug regulatory agency. The result showed that a-zaki tempeh household producer were categorized into level III of IRTP due to 10 minors deviations, 3 major deviations, 4 serious deviations, and 0 critical deviations so that an internal audit needs to be held every 2 weeks. For HACCP, the producer had not yet designed and implemented HACCP plan.